Functional cation defects engineering in TiS2 for high-stability anode. (January 2020) - Liu, Tingting; Zhang, Xikun; Xia, Maoting; Yu, Haoxiang; Peng, Na; Jiang, Cheng; Shui, Miao; Xie, Ying; Yi, Ting-Feng; Shu, Jie
Abstract: In recent years, potassium-ion batteries have been extensively studied as an alternative for lithium ion batteries, thus developing electrode materials for them has become important. TiS2 as a typical electrode material is chosen due to the unique layered structure. However, 1T-TiS2 (tetragonal (T)) is a metastable metallic phase, leading to poor long-term stability for alkali metal ions batteries. In order to alleviate this shortcoming, the functional cation defects are generated on the surface of TiS2 via thermal annealing method in this work. Introduced titanium vacancies effectively improve cycle ability and enhance kinetic performance. The microscopic stress and strain can be weakened due to the existence of defects, demonstrating that defects can alleviate volume expansion during the ion intercalation process to maintain structural stability, thus obtaining excellent cycle ability. Meanwhile, titanium vacancies also can regulate alkali metal ions insertion sites to stabilize crystal structure. In addition, titanium vacancies could be conducive to the improvement of kinetics, including charge-transfer resistance and ions transport. These features are verified by electrochemical analysis combined with density functional theory calculations. Therefore, functional cation defects engineering as a facile and effective strategy can be advanced in various energy storage applications. Graphical abstract: Image 1 Highlights: Functional cation defects are generated via a thermal annealing method. The cycle ability of potassium-ion batteries is doubled by functional cation defects. Functional cation defects can affect the selection of insertion sites based on the different ionic radius. Functional cation defects can enhance electronic conductivity and promote ions transport.